2012
DOI: 10.1002/pssb.201200377
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Lorch‐window method revealing the off‐octahedral Ge in nanocrystalline Ge2Sb2Te5

Abstract: Traditional Lorch‐window technique was modified to the truncated Lorch‐window through various truncation ranges to apply the Lorch‐window functions. The terminal ripples in radial distribution functions (RDFs) were weakened and the shoulder peak at 2.6 Å in crystalline Ge2Sb2Te5 (GST) was revealed by the indication of the off‐octahedral Ge. The Cs‐corrected high resolution transmission electron microscopy image and the corresponding simulations suggest that the off‐octahedral Ge atoms are indeed in the tetrahe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several proposed models agree on well‐ordered Te sublattice and a mixture of Sb, Ge, and vacancies on the other sublattice. In addition to that some of recent studies have shown the different chemical nature of Ge atom and the importance in the GST might form a heterogeneous structural picture that might envision a fast switching arising from a partial bonding rearrangement.…”
Section: Resultsmentioning
confidence: 97%
“…Several proposed models agree on well‐ordered Te sublattice and a mixture of Sb, Ge, and vacancies on the other sublattice. In addition to that some of recent studies have shown the different chemical nature of Ge atom and the importance in the GST might form a heterogeneous structural picture that might envision a fast switching arising from a partial bonding rearrangement.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, Lang et al showed that the local tetrahedral configuration of Ge is unstable in the crystalline environment (although there has been recent controversy on this topic, see Refs. 7–9). Bichara et al 10 found octahedral units in the liquid phase, whereas Caravati et al 11 found both tetrahedral and octahedral atomic environments in amorphous GST.…”
Section: Nanoscale Phase‐transformationmentioning
confidence: 99%
“…Great efforts have been made to chemically/structurally tailor material toward multifunctional practicing. Ge 2 Sb 2 Te 5 chalcogenide is one of the prototype materials for phasechange random access memory (PRAM; Sun et al, 2006;Wuttig et al, 2006;Zhang et al, 2007;Song et al, 2008;Zhang et al, 2008;Liu et al, 2012;Wuttig, 2012;Yamada, 2012). Considering that Ge 2 Sb 2 Te 5 locates in the theoretical pseudo-binary (GeTe) m (Sb 2 Te 3 ) n homologous series (Eom et al, 2006;Silva et al, 2008), it is of great interests to experimentally separate the two components.…”
mentioning
confidence: 99%